Formation of the Company’s Competitive Advantages in the Supply Chain Management and Digital Economy - Roman Nikulin; Nailya Bagautdinova (International Journal of Supply Chain Management, 2019)
The article reveals basic competitiveness elements of modern enterprises in the digital economy and its effects on the supply chain strategy. Currently, the search for new sources of competitiveness focuses not only on the field of scientific, technological and innovation policies of the enterprise, but also on the Internet space, which forms new digital formats of intra-and inter-process interaction. The authors emphasize the basic elements of competitiveness in the digital economy: virtual ecosystems, platform enterprises, digital resources, Smart management. The article presents various approaches to the concept of "digital economy" and trends that put an effect on formation of competitiveness. It is concluded that the digital economy is a "digital" system of economic relations based on the use of information and communication technologies. Digital companies are becoming economic agents of the digital economy. The basic elements of a digital company are infrastructure (Internet access, SOFTWARE, telecommunications), e-business (conducting business through computer networks), e-Commerce (distribution of goods via the Internet). In a digital company, changes in business processes occur in real time using the enterprise information system. The content and ability of working with it and using it in all business processes are core of organization and its digital asset.